Ellenberg‐type indicator values for European vascular plant species. (11th January 2023) - Tichý, Lubomír; Axmanová, Irena; Dengler, Jürgen; Guarino, Riccardo; Jansen, Florian; Midolo, Gabriele; Nobis, Michael P.; Van Meerbeek, Koenraad; Aćić, Svetlana; Attorre, Fabio; Bergmeier, Erwin; Biurrun, Idoia; et al.
Abstract: Aims: Ellenberg‐type indicator values are expert‐based rankings of plant species according to their ecological optima on main environmental gradients. Here we extend the indicator‐value system proposed by Heinz Ellenberg and co‐authors for Central Europe by incorporating other systems of Ellenberg‐type indicator values (i.e., those using scales compatible with Ellenberg values) developed for other European regions. Our aim is to create a harmonized data set of Ellenberg‐type indicator values applicable at the European scale. Methods: We collected European data sets of indicator values for vascular plants and selected 13 data sets that used the nine‐, ten‐ or twelve‐degree scales defined by Ellenberg for light, temperature, moisture, reaction, nutrients and salinity. We compared these values with the original Ellenberg values and used those that showed consistent trends in regression slope and coefficient of determination. We calculated the average value for each combination of species and indicator values from these data sets. Based on species' co‐occurrences in European vegetation plots, we also calculated new values for species that were not assigned an indicator value. Results: We provide a new data set of Ellenberg‐type indicator values for 8908 European vascular plant species (8168 for light, 7400 for temperature, 8030 for moisture, 7282 for reaction, 7193 for nutrients, and 7507 for salinity), of which 398 species have been newly assigned to at least one indicator value. Conclusions: The newly introduced indicator values are compatible with the original Ellenberg values. They can be used for large‐scale studies of the European flora and vegetation or for gap‐filling in regional data sets. The European indicator values and the original and taxonomically harmonized regional data sets of Ellenberg‐type indicator values are available in the Supporting Information and the Zenodo repository. Abstract : This paper introduces a harmonized data set of Ellenberg‐type indicator values applicable at the European scale. We collected 13 regional data sets of indicator values for vascular plants compatible with Ellenberg scales and calculated a new data set of Ellenberg‐type indicator values for 8, 908 European vascular plant species.